(untitled) - edited by Jeff Good (New York, 2008)
Universals constrain change; change results in typological generalizations / Paul Kiparsky -- On the explanation of typologically unusual structures / Alice C. Harris -- Consonant epenthesis / Juliette Blevins -- Formal universals as emergent phenomena / Joan L. Bybee -- Paradigmatic uniformity and markedness / Andrew Garrett -- Explaining Universal Tendencies and Language Particulars in Analogical Change / Adam Albright -- Creating Economical Morphosyntactic Patterns in Language Change / Martin Haspelmath -- On the explanatory value of grammaticalization / Tania Kuteva and Bernd Heine -- The classification of constituent order generalizations and diachronic explanation / John Whitman -- Emergent serialization in English / Paul J. Hopper -- Universals and diachrony / Johanna Nichols
Keywords: Linguistic universals; Linguistic change; Typology (Linguistics)